PERDAGANGAN SAHAMNYA (STUDI SAHAM POLA SYARI’AH BURSA EFEK INDONESIA JAKARTA). - Prayudha Ananta; Deris Desmawan (FEB Universitas Sultan Ageng Tirtayasa, 2017)
The aims of this research are to measurement securities risk, and determinethe impact of the stock of risk to the volume of syari’ah stock trades in BEI Jakarta, when used stock return and rate of deposit interest as are moderating ore controlling variable.Sample size of the issuer is purposive 4 corporate from 30 issuer of existing liquid, that four sample is selected by simple random. Analysis tool used is multiple regression. From the partial test results to variable risk-free stock, stock return, and deposit interest rate (as risk-free return) significantly affect the volume of stock trading that four issuer sample. Stock systematic risk-free variable and deposit interest rate adversely affect the trading volume of shares of each issuer. Otherwise, magnitude of stock returns negatively affect the trade volume of each issuer's stock. This suggests that the interest of investors to trade and investing in Jakarta Islamic Index (JII), that would still pay attention to these factors.Keywords: Syari’ah Stock,Systematic Risk, Stock Return